A comparative evaluation of the leadership development needs of basic school leaders in the 4.0 era - Awodiji, Omotayo A.; Naicker, Suraiya R. (Frontiers in Education, 2024)
School leadership development (SLP) in the context of the Fourth Industrial Revolution (4.0) is a crucial aspect of preparing basic school leaders to navigate the challenges and opportunities presented by the rapid technological advancements and changes in the modern world. The 4.0 is characterized by the fusion of digital, physical, and biological technologies, which profoundly impact various aspects of society, including education. Thus, this study examined basic school leaders’ development needs in 4.0 in Nigeria and South Africa. A comparative research approach of survey design was adopted with the aid of a questionnaire. Descriptive statistics (mean score) and an independent t-test were used to analyze the collected data. Results indicated that basic school leaders in South Africa fared better than their counterparts from Nigeria regarding their 4.0 knowledge. However, no significant difference was found in 4.0 leadership skills. Leaders from both nations indicated the need for development programs in technological applications to enhance competency to perform their administrative tasks. In theory, the study addresses African schools’ 4.0 leadership needs. To lead education into the future, each nation must also understand the specific 4.0 leadership skills its school leaders will need. In light of the study’s findings, policymakers should consider what gaps need to be filled to equip their basic school leaders with Education 4.0 skills.